2007
DOI: 10.1007/s11434-007-6017-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon accumulation in deep fluid modified carbonate rock in the Tarim Basin

Abstract: The activities of deep fluid are regionalized in the Tarim Basin. By analyzing the REE in core samples and crude oil, carbon isotope of carbon dioxide and inclusion temperature measurement in the west of the Tazhong Uplift in the western Tarim Basin, all the evidence confirms the existence of deep fluid. The deep fluid below the basin floor moved up into the basin through discordogenic fault and volcanicity to cause corrosion and metasomatosis of carbonate rock by exchange of matter and energy. The pore struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Karst was well developed in Ordovician, so it can be preferable for reservoirs. Lunnan-Tahe oilfield is considered as the biggest one with Paleozoic marine carbonate reservoirs in China (Lü et al, 2007;Liang, 2008;Jin et al, 2009). Thick sediments in Mesozoic and Cenozoic became a good regional cap rocks, so that oil and gas had been well preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Karst was well developed in Ordovician, so it can be preferable for reservoirs. Lunnan-Tahe oilfield is considered as the biggest one with Paleozoic marine carbonate reservoirs in China (Lü et al, 2007;Liang, 2008;Jin et al, 2009). Thick sediments in Mesozoic and Cenozoic became a good regional cap rocks, so that oil and gas had been well preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Ordovician hydrocarbon reservoirs in the Tarim Basin are significantly influenced by magmatism and associated hydrothermal activity [18][19][20]. Hydrothermal activity resulted in the precipitation of minerals such as calcite, and it created a high-temperature environment that was favorable for the occurrence of TSR in the reservoirs [13][14][15][16][17][18][19]. TSR is an important process for the formation of pyrite in the Ordovician reservoirs, and pyrites of TSR genesis are characterized by enriched sulfur isotope compositions [13,15,18,19].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Pyrite is widely distributed in Ordovician hydrocarbon-bearing carbonate rocks within the Tarim Basin, North West (NW) China, and the precipitation of pyrite is closely associated with hydrocarbons [13][14][15][16][17][18][19]. Previous petrographic and isotopic studies have shown that there are two groups of pyrite; these are (i) by-products of thermochemical sulfate reduction (TSR) and (ii) bacterial sulfate reduction (BSR), respectively [13][14][15][16][17][18][19]. Sulfate minerals can be reduced to hydrogen sulfide (H 2 S) by hydrocarbons either through bacterial metabolism (i.e., BSR) or thermochemical pathway (i.e., TSR) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, carbonate reservoirs in the Tarim Basin are found mainly along fault zones, unconformities, biohermal suites, fracture zones and near effective source rocks (Lü and Jin, ). Carbonate plays have been widely studied in China (Yang et al ., , ; Chi et al ., ; Lü et al ., , , , ; Zhao et al ., ; Chen et al ., ; Han et al ., ; Zou and Tao, ; Luo et al ., ; Zhao, ; Gu et al ., ; Zhang and Liu, ). At a great burial depth and high degree of diagenesis, primary pores in carbonate reservoir beds have nearly disappeared, and reservoir beds depend on secondary pores or fractures (Pang, ).…”
Section: Introductionmentioning
confidence: 99%